Polygamy in the Perspective of Hadith: Justice and Equality among Wives in A Polygamy Practice - Husain, Rahmin T.; Ahmad, Arifuddin; Kara, Siti Aisyah; Alwi, Zulfahmi (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2019)
This article aims to overview some hadith[s] concerning justice and equality among wives in the practice of polygamy. This is literature-based research. In this study, documentation technique was employed in order to collect the data and used takhrij al-Hadith approach. Then, they were analysed by using descriptive analysis method. The result reveals that polygamy might be allowed in certain conditions, especially when a husband could be just and equal in a household among his wives. Practically, this requirement is somewhat challenging. Besides faith and obedience, justice and equality in a family can only be achieved if there is a high optimism, strong confidence, and good paradigm. Although some wives consider it as ‘ain al-sukhty (hatred paradigm), others percieve it as ‘ain al-ridha (pleased paradigm). Unfortunately, to overcome this problematic matter for polygamists in the recent day, justice and equality as the key points in a household should realistically be understood well as what the Prophet Muhammad Peace Be Upon Him (PBUH) had practiced. A positive atmosphere is likely possible to realize in a polygamous household.